2016
DOI: 10.1136/bmjopen-2015-010975
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dermatitis in submariners during a submerged patrol: an observational cohort study

Abstract: ObjectiveThe aim of this pilot study was to determine risk factors, including Staphylococcus aureus nasal carriage, for dermatitis in submariners during a submarine patrol.Participants and methods36 submariners undertaking a submerged 6-week patrol participated in the study. Severity of dermatitis and its impact was assessed using visual analogue scales and questionnaires at baseline and weekly throughout the patrol. S. aureus carriage levels in submariners were determined by nasal swabbing at baseline and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In contrast, other studies suggest that decolonization of S. aureus did not reduce the incidence of surgical site infections [3] or skin and soft tissue infections [8]. In a UK submariner cohort work has shown that nasal carriage of S. aureus was not identified as a risk factor for worsening skin health, potentially questioning the impact of decolonization [25]. In our cohort we found persistent carriers of S. aureus were less likely to develop an SSTI potentially refuting the role for decolonization and suggesting that further studies are warranted to investigate if carriage has some protective effect.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, other studies suggest that decolonization of S. aureus did not reduce the incidence of surgical site infections [3] or skin and soft tissue infections [8]. In a UK submariner cohort work has shown that nasal carriage of S. aureus was not identified as a risk factor for worsening skin health, potentially questioning the impact of decolonization [25]. In our cohort we found persistent carriers of S. aureus were less likely to develop an SSTI potentially refuting the role for decolonization and suggesting that further studies are warranted to investigate if carriage has some protective effect.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we noted that the persistent carriers of S. aureus throughout training were less likely to develop an SSTI than non-carriers. This potentially raises questions about the aetiology of these infections and the putative protective effects of S. aureus carriage in certain population groups and the role for decolonization [25].…”
Section: Discussionmentioning
confidence: 99%